Advances in experimental philosophy of medicine - Hens, Kristien; Block, Andreas (Bloomsbury, 2023)
While experimental philosophy of science is an established field, attempts to tackle issues in philosophy of medicine from an experimental angle are still surprisingly scarce. A team of interdisciplinary scholars demonstrate how we can make progress by integrating a variety of methods from experimental philosophy, including experiments, sociological surveys, simulations, as well as history and philosophy of science, in order to yield meaningful results about the core questions in medicine. They focus on concepts central to philosophy of medicine and medical practice, such as death, pain, disease and disorder, advance directives, medical explanation, disability and informed consent. Presenting empirical findings and providing a crucial foundation for future work in this dynamic field, this collection explores new ways for philosophers to cooperate with scientists and reveals the value of these collaborations for both philosophy and medicine.